THE CHCC Project: Developing the Collection of Historical and Contemporary Census Data and Related Materials into a Major Learning and Teaching Resource - Carter, Jackie; Brown, Mark; See, Linda; Russell, Lani (Proceedings of the International Conference on Networked Learning, 2002)
The UK academic community has access to a Collection of Historical and Contemporary Census Data and related resources (CHCC), which are available in digital format. Although individual datasets have been used extensively in research they have been significantly under-used in teaching and learning. To address this, the CHCC Project has been funded by JISC, under its Developing the DNER for Learning and Teaching initiative. The project involves six partners from four UK Universities and runs from October 2000 until September 2003.